2017
DOI: 10.1038/ncomms13994
|View full text |Cite
|
Sign up to set email alerts
|

Regional adaptation defines sensitivity to future ocean acidification

Abstract: Physiological responses to temperature are known to be a major determinant of species distributions and can dictate the sensitivity of populations to global warming. In contrast, little is known about how other major global change drivers, such as ocean acidification (OA), will shape species distributions in the future. Here, by integrating population genetics with experimental data for growth and mineralization, physiology and metabolomics, we demonstrate that the sensitivity of populations of the gastropod L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 64 publications
1
55
0
Order By: Relevance
“…Variability between individuals is emerging as an important theme in climate change studies due to its role as a driver of resilience or adaptation within populations and species (Calosi et al, ; CaraDonna, Iler, & Inouye, ; Inouye, ; Kroeker, Kordas, Crim, & Singh, ; Ovaskainen et al, ; Vargas et al, ). However, not only does individual variability exist in climate change responses, it may affect ecological function under climate stress (CaraDonna et al, ; McCoy & Kamenos, ; McCoy, Kamenos, Chung, Wootton, & Pfister, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability between individuals is emerging as an important theme in climate change studies due to its role as a driver of resilience or adaptation within populations and species (Calosi et al, ; CaraDonna, Iler, & Inouye, ; Inouye, ; Kroeker, Kordas, Crim, & Singh, ; Ovaskainen et al, ; Vargas et al, ). However, not only does individual variability exist in climate change responses, it may affect ecological function under climate stress (CaraDonna et al, ; McCoy & Kamenos, ; McCoy, Kamenos, Chung, Wootton, & Pfister, ).…”
Section: Discussionmentioning
confidence: 99%
“…Variability between individuals is emerging as an important theme in climate change studies due to its role as a driver of resilience or adaptation within populations and species (Calosi et al, 2017;CaraDonna, Iler, & Inouye, 2014;Inouye, 2008;Kroeker, Kordas, Crim, & Singh, 2010;Ovaskainen et al, 2013;Vargas et al, 2017 those that are more productive at elevated temperatures are also more productive in control temperatures (Clark et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In terrestrial studies, Franco et al (2006) showed that three out of four butterfly species are reported extinct or showed drastic distributional changes due to climate change along with habitat degradation and loss. Previous research has also found that different populations of the same species respond differently to altered environmental conditions (Bozinovic, Calosi, & Spicer, 2011;Calosi et al, 2017;Gaston, 2009). Previous research has also found that different populations of the same species respond differently to altered environmental conditions (Bozinovic, Calosi, & Spicer, 2011;Calosi et al, 2017;Gaston, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Even under strong selective pressure and with high levels of mortality, six generations appears to be too short a time frame to observe genetic adaptation in O. labronica. The differential survival of individuals shows that phenotypic plasticity is sufficient to prevent extinction at a population level and to provide a temporal buffer for genetic variation to respond via natural selection (PadillaGamiño et al, 2016;Calosi et al, 2016b). Measuring life-history and physiological traits simultaneously, using a multi-factorial experimental design, enables us to dissect how plasticity to one driver influences a species' response to another, from one generation to another.…”
Section: −1mentioning
confidence: 99%